The Impact of Federal Fund Rate in U.S.A. Movements on Lending Rates and Consumer Price Index in Jordan - Khasawneh, Malik Qasim (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
This study measures the impact of the federal fund rate on the lending rate and the consumer price index in Jordan during the period 1994-2013, relying on monthly data. The study finds that common changes that occur in the U.S. federal fund rate lead to direct changes in the lending rate in Jordan, and these changes are statistically significant. The study also finds that the changes in the U.S. federal fund rate lead to direct changes also in the consumer price index and these changes also are statistically significant.